2016
DOI: 10.3390/ijms17101766
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Non-Pharmacological Interventions on Brain-Derived Neurotrophic Factor in Schizophrenia: A Systematic Review and Meta-Analysis

Abstract: Several studies have investigated the relationship between non-pharmacological interventions (NPIs) and peripheral brain-derived neurotrophic factor (BDNF) in schizophrenia patients. We conducted a systematic review and meta-analysis to review the efficacy of NPIs on peripheral serum and plasma BDNF in subjects with schizophrenia (including schizoaffective disorder). Meta-analyses were conducted to examine the effects of NPIs on blood BDNF levels by using the standardized mean differences (SMDs) between the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 76 publications
0
18
0
Order By: Relevance
“…One region that has been implicated is the hippocampus [87] although a meta-analysis of four studies did not support this hypothesis [44]. This review [69] also found inconsistent evidence for an effect of exercise on BDNF levels, which is consistent with a meta-analysis [72] (AMSTAR 10, evidence level -1) also finding that exercise did not influence BDNF levels. Thus, whilst there seems reasonable evidence that exercise does improve cognition in schizophrenia-spectrum disorders [67], the underlying mechanisms are not yet clear.…”
Section: Schizophrenia-spectrum Disordersmentioning
confidence: 57%
See 2 more Smart Citations
“…One region that has been implicated is the hippocampus [87] although a meta-analysis of four studies did not support this hypothesis [44]. This review [69] also found inconsistent evidence for an effect of exercise on BDNF levels, which is consistent with a meta-analysis [72] (AMSTAR 10, evidence level -1) also finding that exercise did not influence BDNF levels. Thus, whilst there seems reasonable evidence that exercise does improve cognition in schizophrenia-spectrum disorders [67], the underlying mechanisms are not yet clear.…”
Section: Schizophrenia-spectrum Disordersmentioning
confidence: 57%
“…1). Overall, 20 systematic reviews and meta-analyses were included in this guidelines document, which included studies that provided effect sizes for the benefit of exercise for SMI [51] (N = 1), schizophreniaspectrum disorders [67][68][69][70][71][72][73] (N = 7), BD [74,75](N = 2) and MDD [76][77][78][79][80][81][82][83][84][85] (N = 10).…”
Section: Search Results and Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a recent study with cyclists detected acute BDNF release during exercise and showed that intensified training improved the athletes' mood state, however, without modifying their plasma BDNF levels (Piacentini et al, ). The time latency for serum BDNF changes in response to behavioral and cognitive interventions is not clear‐cut and probably varies according to the health condition of the individual and the type of therapy (Hakansson et al, ; Kobayashi et al, ; Sanada et al, ; Turakitwanakan, Mekseepralard, & Busarakumtragul, ; Yamada, Yoshimura, Nakajima, & Nagata, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, circulating BDNF has been proposed as a potential biomarker for neuro-psychiatric disorders and neurodegenerative diseases [22,23,24,25,26,27]. On the contrary, the relationship between circulating BDNF and cardiometabolic disorders is still unclear.…”
Section: Introductionmentioning
confidence: 99%